PENGELOLAAN KARAKTERJUJUR DAN TANGGUNG JAWAB DALAM PEMBELAJARAN DI SD MUHAMMADIYAH 16 SURAKARTA - NGATMANTO, NGATMANTO (2016)
This research is closely linked to moral and character siswa.Dalam framework of healthy competition and improving the quality of schools in order to maintain the existence and recognition of the public schools must continue to innovate pendidikan.Tujuan pursue accelerated progress of this research to: 1) describe how to improve the quality of educational institutions 2) describe ways that the public interest 3) provides an overview of benefits and 4) describe the factors that far ahead goal past about the importance of children's character both in learning and subsequent dikehidupan. This study used a qualitative approach, the subject of this study is SD Muhammadiyah Surakarta 16 Karangasem. The sources of data used in this study are informan, document and events. While the techniques for collecting data are interviewing, documentation and observation. The collected data are analysed by using interactive analysis. The results of the research show that to improve the quality must implement three main steps, they are quality improvement models that are applied through improved model of learning, habituation or school culture, and the adoption of honest character and responsibility in learning. Through the character bulding awakened a) Personal honest will be respected everyone b) The person who is able to be liable for any actions c) Chick generation of people that are reliable d) become future leaders of authoritative e) would create the nation state respected by the nations of the world.